How my library grew, by Dinah : story and pictures / by Martha Alexander. - Alexander, Martha, 1920-2006 (H.W. Wilson Co., 1983)
Neither Dinah nor her Teddy Bear have ever been to a library, but when one is built just down the street, she looks forward to the opening day.
Keywords: Libraries -- Juvenile fiction.; Libraries.; Fiction.; Juvenile works.